2010
DOI: 10.1590/s0004-28032010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Grade of esophageal cancer and nutritional status impact on postsurgery outcomes

Abstract: -Context -Undernutrition is a well known underlying cause in both disease onset and outcome. Objective -To associate disease severity with pre surgical nutritional status, the main postsurgical complications, and mortality in esophagus cancer patients. Method -Retrospective data from 100 patients (38-81 years old, 85% males) who had undergone esophagectomy (G1/n = 25) or gastro/jejunostomy (G2/n = 75) between 1995 and 2004. Data included clinical, endoscopic, histological (TNM-UICC), dietary, anthropometric, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
18
1
2
Order By: Relevance
“…Many studies have demonstrated lower mortality in patients with lower body weight loss, despite in some cases, as in a study with surgical patients with esophagus cancer, this was not observed 21 . Considering that to calculate the Nutritional Risk Index both serum albumin and body weight loss are needed, the Nutritional Risk Index result might overestimate malnutrition, because, albumin level might be related with disease severity and body weight loss estimation depends on subjective usual body weight value informed by the patient.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Many studies have demonstrated lower mortality in patients with lower body weight loss, despite in some cases, as in a study with surgical patients with esophagus cancer, this was not observed 21 . Considering that to calculate the Nutritional Risk Index both serum albumin and body weight loss are needed, the Nutritional Risk Index result might overestimate malnutrition, because, albumin level might be related with disease severity and body weight loss estimation depends on subjective usual body weight value informed by the patient.…”
Section: Discussionmentioning
confidence: 90%
“…Mortality is higher in subjects with lower serum albumin level 21 . Gregg 15 assessed several mortality predictors and found that serum albumin had a positive association with mortality in patients submitted to cystectomy 21 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations